Fabrication of micro segment structured DLC film - Yumi YOSHIDA (The Japan Society of Mechanical Engineers, 2015)
DLC films have many excellent properties, such as high wear resistance and a low friction coefficient, and are used in an increasing range of application fields. However, their low transmission of visible light prevents DLC films from being used for transparent materials. Nano-segment structured DLC (S-DLC) film with a segmented pitch equal to or less than the wavelength of visible light is supposed to not only solve this problem but also improve its mechanical properties. In this study as preliminary stage of nano S-DLC film, we fabricated DLC films consisting of 1-μm-size segments which have not only high wear resistance but also unique optical characteristics. This structure on DLC film was fabricated by electron beam lithography followed by liftoff method, which is suitable for nanoscale micromachining. The micro segment structured DLC films with groove width of 1 μm and pitch of 20 μm had rounded edges because the resist mask acted as an electrode. Micro S-DLC film exhibited structural colors because of the reflection-type diffraction grating and its transmittance was lower than that of continuous DLC films. From ball on disk test, it was found that the wear resistance of the micro S-DLC film with a groove of 1 μm was superior to that of a normal continuous DLC film and the small edge curvature could improve wear resistance furthermore.